Morus alba: natural and valuable effects in weight loss management - Ntalouka, Foteini; Tsirivakou, Athina (Frontiers in Clinical Diabetes and Healthcare, 2024)
Overweight and obesity are conditions associated with serious comorbidities, such as diabetes and cardiovascular disease. Prevalence of excessive fat accumulation is increasing worldwide, and thus the need for efficient and sustainable weight loss regimes has become a major issue in clinical practice. Despite the important advances in the development of anti-obesity medications (AOM), their side effects, cost, and accessibility, are limiting factors for their routine use. Conversely, the studies of medicinal plants for weight management holds strong promise as a growing area of research. This review consolidates the representative evidence about the beneficial impacts of Morus alba on weight management and associated metabolic parameters, encompassing: inhibition of digestive enzymes, and thus contribution to the energy deficit required for weight loss, improvements in glucose and lipid metabolism, and attenuation of adiposity. Findings from in vitro, in vivo, and clinical investigations reviewed in the paper, demonstrate that white mulberry extracts have the potency to supplement efficiently and safely a healthy weight management approach.